Applied mathematics for the managerial, life, and social sciences : interactive video skillbuilder CD ROM with graphing calculator tutorial for TAN4 - S.T. Tan (Thomson, 2007)
Berisi Tan applied Mathematics dan Remove Tan applied mathematics 4e